Patients with AIDS‐defining cancers are not universally screened for HIV: a 10‐year retrospective analysis of HIV‐testing practices in a Swiss university hospital. Issue 10 (8th August 2014) - Mosimann, V; Cavassini, M; Hugli, O; Mamin, R; Achtari, C; Peters, S; Darling, KEA
Abstract : Objectives: Kaposi's sarcoma (KS), invasive cervical carcinoma (ICC) and non‐Hodgkin lymphoma (NHL) have been listed as AIDS‐defining cancers (ADCs) by the Centers for Disease Control and Prevention since 1993. Despite this, HIV screening is not universally mentioned in ADC treatment guidelines. We examined screening practices at a tertiary centre serving a population where HIV seroprevalence is 0.4%. Methods: Patients with KS, ICC, NHL and Hodgkin lymphoma (HL), treated at Lausanne University Hospital between January 2002 and July 2012, were studied retrospectively. HIV testing was considered part of the oncology work‐up if performed between 90 days before and 90 days after the cancer diagnosis date. Results: A total of 880 patients were examined: 10 with KS, 58 with ICC, 672 with NHL and 140 with HL. HIV testing rates were 100, 11, 60 and 59%, and HIV seroprevalence was 60, 1.7, 3.4 and 5%, respectively. Thirty‐seven patients (4.2%) were HIV‐positive, of whom eight (22%) were diagnosed at oncology work‐up. All newly diagnosed patients had CD4 counts < 200 cells/μL and six (75%) had presented to a physician 12–236 weeks previously with conditions warranting HIV testing. Conclusions: In our institution, only patients with KS were universally screened. Screening rates for other cancers ranged from 11 to 60%. HIV seroprevalence was at least fourfold higher than the population average. As HIV‐positive status impacts on cancer patient medical management, HIV screening should be included in oncology guidelines. Further, we recommend that opt‐out screening should be adopted in all patients with ADCs and HL.